Social Class, Amish Culture, and an Egalitarian Ethos: Case Study from a Rural School Serving Amish Children - Aimee Howley; Craig Howley; Larry Burgess; Drew Pusateri (Journal of Research in Rural Education, 2008)
This article presents a case study of egalitarian educational practices evident in a rural school that served a large proportion (40%) of Amish students. The Amish are a pacifi st Christian sect widely misunderstood as quaint and even backward; their traditional work is small-scale farming. In 1972 the Amish wrested the national right"via a US Supreme Court case"to educate their children only through 8th grade, and in their own schools. Given this struggle, the fact that some Amish families would elect to send their children to public schools (which their taxes support) might be regarded as surprising. The school"one of six in a larger study"described in this article took careful measures, however, to welcome Amish children and families, even to the extent of establishing a unique seventh and eighth grade curriculum for them (and thus returning seventh and eighth grade instruction to an elementary school setting). The focus of this study was to characterize (primarily via the analysis of interview transcripts) the school's educational practice. Four themes emerged from the analysis of transcripts: (1) "in league with parents," (2) "teaching agrarian values," (3) "educating for community participation," and (4) "embracing all children." These themes were, in fact, the obverse of those that characterized the other fi ve schools represented in the overall data set, making it by far the most egalitarian school studied.